3+9(7c-4)=8-15c

Simple and best practice solution for 3+9(7c-4)=8-15c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+9(7c-4)=8-15c equation:


Simplifying
3 + 9(7c + -4) = 8 + -15c

Reorder the terms:
3 + 9(-4 + 7c) = 8 + -15c
3 + (-4 * 9 + 7c * 9) = 8 + -15c
3 + (-36 + 63c) = 8 + -15c

Combine like terms: 3 + -36 = -33
-33 + 63c = 8 + -15c

Solving
-33 + 63c = 8 + -15c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '15c' to each side of the equation.
-33 + 63c + 15c = 8 + -15c + 15c

Combine like terms: 63c + 15c = 78c
-33 + 78c = 8 + -15c + 15c

Combine like terms: -15c + 15c = 0
-33 + 78c = 8 + 0
-33 + 78c = 8

Add '33' to each side of the equation.
-33 + 33 + 78c = 8 + 33

Combine like terms: -33 + 33 = 0
0 + 78c = 8 + 33
78c = 8 + 33

Combine like terms: 8 + 33 = 41
78c = 41

Divide each side by '78'.
c = 0.5256410256

Simplifying
c = 0.5256410256

See similar equations:

| 6/2x-1=3 | | (x/5)6=90 | | n+33=24 | | 3x-7=2+3(1+x) | | h(t)=-5t^2+15t+50 | | 3x+15=4x-18 | | f(X)=325 | | 7X-3=3X+6 | | 5(x-2)-3(x+5)=7-x | | f(325)= | | 3=-9+5*-3+c | | 3=-9+5x-3+c | | -2(w+1)=-5w-26 | | 4d-8=-12 | | 6a+15=4b | | -9+2y=-6 | | 87=4u+15 | | 3x(2y-5x)= | | 2u-14=4(u-1) | | 3u-17=16 | | 4f+3(f-5)= | | -7(x+4)=-2x-33 | | 21x-63=-14 | | 4(x+6)+2(x-3)=3(x+6) | | 16=2v+10 | | 41=4X-3Y | | 6nx(-4)= | | 48x=496+x^2 | | 4.2t-7=11-3.3t | | 13+2x=2(-x+6)-31 | | 3(2x-1)=x/2 | | (X-2)*5= |

Equations solver categories